Repurposing of a drug scaffold: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, Remya; Shingare, Rahul D.; Kumar, Vinod; Anand, Amitesh; Swetha, B.; Veeraraghavan, Sridhar; Viswanadha, Srikant; Ummanni, Ramesh; Gokhale, Rajesh S.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2016)
The structural similarity between an MmpL3 inhibitor BM212, and a cannabinoid receptor modulator rimonabant, prompted us to investigate the anti-tubercular activity of rimonabant and its analogues. Further optimization, particularly through incorporation of silicon into the scaffold, resulted in new compounds with significant improvement in anti-tubercular activity against Mycobacterium tuberculosis (H37Rv). The sila analogue 18a was found to be the most potent antimycobacterial compound (MIC, 31 ng/mL) from this series with an excellent selectivity index. (C) 2016 Elsevier Masson SAS. All rights reserved.

Route to benzimidazol-2-ones via decarbonylative ring contraction of quinoxalinediones: application to the synthesis of flibanserin, A drug for treating hypoactive sexual desire disorder in women and marine natural product hunanamycin analogue - Shingare, Rahul D.; Kulkarni, Akshay S.; Sutar, Revannath L.; Reddy, D. Srinivasa (ACS Omega, 2017)
A simple and practical method to access a variety of benzimidazol-2-ones is reported here. A series of N-alkylsubstituted benzimidazol-2-ones were synthesized by decarbonylative ring contraction starting from corresponding quinoxalinediones for the first time. The utility of the method has been demonstrated by synthesizing recently approved controversial drug flibanserin (Addyi) and a urea analogue of marine antibiotic natural product hunanamycin-A.

Route to access imidazol[1,5-a]indole-1,3-diones and pyrrolo[1,2-c]imidazole-1,3-diones - Rao, Ramana Sreenivasa; Shajan, Fere Joseph; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2019)
A novel and practical route to synthesize imidazol[1,5-a]indoles and pyrrolo[1,2-c]imidazoles via N-H functionalization has been developed. Indole-2-carboxylic acid or pyrrole-2-carboxylic acid with diverse aniline groups and carbonyldiimidazole (CDI), in the presence of a base under microwave conditions, resulted in imidazol[1,5-a]indoles and pyrrolo[1,2-c]imidazoles, respectively. The present method is free of work-up and no need for column chromatography. Both title scaffolds can serve as useful heterocyclic scaffolds in medicinal chemistry as such, or they can be used as building blocks to construct different classes of useful compounds.

Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.

Ready access to densely substituted furans using Tsuji-Wacker type cyclization - Masal, Dattatraya P.; Choudhury, Rahul; Singh, Aman; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
A competent method for the construction of highly substituted furans catalyzed by Pd(II) and Cu(II) chloride has been developed. The method provides easy access to di-, tri-, and tetrasubstituted furans from corresponding diols with relatively mild conditions in a unified strategy. The developed method has been successfully tested with more than 25 substrates, which resulted in furans of multiple substitution patterns with up to 84% isolated yields.

Ready access to benzodiazocines from tryptamines: a druggable scaffold toward antiviral agents - Saranya, N. Sathya Sai; Choudhury, Rahul; Routholla, Ganesh; Supekar, Prathmesh R.; R, Nandhakumaar; Martin, Alna Kuriyickal; Muruganandham, Renuga Devi; Kumar, Bokara Kiran; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2025)
Herein we report the first synthesis of the proposed structure of a benzodiazocine natural product, peganutonin A. Considering the druggable nature of benzodiazocine and its limited exploration in the field of medicinal chemistry, we generalized the approach and created a library of compounds useful for various biological activities. Key steps in present approach include tryptamine cyclization facilitated by tert-butyl hypochlorite and cleavage of the fused indole ring using ozonolysis. Preliminary screening of the synthesized compounds resulted in potent antiviral compounds against the SARS-CoV-2 virus.
Keywords: Benzodiazocine; drug discovery; Indole cleavage; Lipinski's rule of Five; SARS-CoV-2 inhibition; Tryptamine